Understanding K-12 students' information literacy in informal learning environments: a literature review. (22nd April 2020) - Zhu, Sha; Wu, Di; Yang, Harrison; Li, Yang; MacLeod, Jason
Information literacy has long been considered as a set of decontextualised skills from behaviourist perspective, or as a learning process from the constructivist perspective. With both conceptualisations, information literacy research has primarily emphasised formal learning environments. This literature review relies upon socio-cultural theory to expand understanding of K-12 students' information literacy within the under-represented perspective of informal learning environments, such as homes, public properties, and online spaces. Guided by the research questions, the inclusion and exclusion criteria were identified to select the related literatures for review. The literature review shows that K-12 students engage in a range of digital meaning-making practices in informal learning environments. It is recommended that the evaluation standards and approaches for students' information literacy should be changed, and a collaborative relationship should be established among schools, families, and the communities for promoting information literacy.